Implementation of Worksheets Based on Experiments on The Subject of Biotechnology to Develop Students' Scientific Literacy - Ngaji, Irma Utu; Mirawati, Baiq; Ratnasari, Desi; Arifin, Ahmad Aris; Fajri, Surya (Lembaga Penelitian dan Pemberdayaan Masyarakat, 2023)
This study aimed at bolstering students' scientific literacy in biotechnology through the implementation of Experiment-Based Learning and Creativity Worksheets (LKPD). Utilizing a classroom action research framework, the investigation was conducted over two cycles, incorporating planning, action, observation, evaluation, and reflection phases. It involved 30 students and used observational sheets for monitoring teacher and student activities, along with multiple-choice and essay questions to assess students' scientific literacy. The findings revealed a notable enhancement in both teaching methods and student learning outcomes, facilitated by the LKPD usage. Specifically, teacher performance improved from achieving 80% of the set criteria in the first cycle to 90% in the second, upgrading their rating from 'Good' to 'Very Good'. This improvement was paralleled by a rise in students' average scores from 85.33 to 90.58, indicating a heightened engagement with and comprehension of biotechnological principles. The employment of LKPDs proved critical not just for expanding knowledge but for the practical application of scientific concepts, as demonstrated by an average literacy score of 88. Furthermore, an uplift in the average scientific literacy score from 76.59 in the first cycle to 84.89 in the second emphasizes the significance of LKPDs in enhancing students' grasp of scientific theories. Overall, the interventions across the cycles successfully elevated the caliber of teaching, enriched the student learning experience, and significantly improved science literacy, thus contributing to an enhancement in educational quality